Infeksi Saluran Kemih pada Kehamilan: Prevalensi dan Faktor-Faktor yang Memengaruhinya - Edy Fakhrizal (Fakultas Kedokteran Universitas Riau, 2017)
To obtain a prevalence of urinary tract infection in pregnancy andits influential risk factors.This is a cross sectionalstudy. The subjects were all pregnant women who came to Obstetric & Gynecology clinic of Arifin Achmad Pekanbaru– Riau Hospital, between June 1st and October 31st 2016. Subjects with appropriate inclusion and exclusion criteriaand agreed to join this study were asked to fill out questionnaire and urinalysis test was done.The data was analyzedwith Stata 12. The distribution of data was analyzed with descriptive univariate and presented in (n) and(%). Bivariateanalysis was done to see any influential risk factors to urinary tract infection in pregnancy. From recruited 74 subjects,27subjects (36,5%) were with urinary tract infection and 4 subject of its (14,8%) was asymptomatic bacteriuria. Theprevalence of urinary tract infection in pregnancy in this study was 36,5% and the influential risk factors wereeducation, occupation, total water consumpted a day, and cleaning vagina before coitus.